Blockchain-BIM: reducing cost in green retrofitting for sustainable construction development - Husin, Albert Eddy; Kristiyanto, Kristiyanto; Kussumardianadewi, Bernadette Detty (SINERGI, 2024)
During the implementation process, the construction sector significantly affects the environment, leading to environmental pollution and the overconsumption of natural resources. This jeopardizes the sustainability of a healthy living environment, requiring a solid system to control development. A sustainable and environmentally friendly development system is crucial from architectural, construction, and economic perspectives. However, when applying the concept of Green Building to existing buildings, the cost of green retrofits has increased by about 10.77%. A case study was carried out on the existing BRIN (National Research and Innovation Agency) building to provide alternative solutions to reduce these green retrofitting costs, making sustainable construction the primary option in developing the construction sector. One way to address this cost increase is using the Blockchain-Building Information Modeling (BIM) application, an alternative method to determine the most economical cost based on input or a given model. BIM models contain non-geometric information, including materials for building components, quantities, prices, procedures, scales, and sizes. This allows for real-time data exchange and collaborative decision-making between stakeholders, improving visualization and modeling and lowering costs due to better construction outcomes and higher productivity probability. The implementation of Blockchain-BIM is expected to result in green retrofit cost savings of at least 3% on each green level according to the Ministry of Public Works and Housing (PUPR) of the Republic of Indonesia Technical Guidelines No. 01/SE/M/2022, namely Primary, Intermediate, and Main.